Comparing risk environments for HIV among people who inject drugs from three cities in Northern Mexico - Angelica Ospina-Escobar; Carlos Magis-Rodríguez; Fatima Juárez; Dan Werb; Sergio Bautista Arredondo; Rubén Carreón; María Elena Ramos; Steffanie Strathdee (BMC, 2018)
Abstract Background A large body of research has investigated the rise of injection drug use and HIV transmission in Tijuana and Ciudad Juarez (CJ). However, little is known about the dynamics of injecting in Hermosillo. This study compares drug-related behaviors and risk environment for HIV of people who inject drugs (PWID) across Tijuana, CJ, and Hermosillo to identify factors that could explain differences in HIV prevalence. Methods Data from Tijuana belong to a prospective study (El Cuete IV). Data from Hermosillo and Ciudad Juarez belong to a cross-sectional study. Both studies collected data in places where PWID spend time. All participants completed quantitative behavioral and serological testing for HIV. Datasets were merged using only comparable variables. Descriptive statistics tests were used to compare sociodemographic and behavioral characteristics of people who inject drugs PWID sampled in each city. A logistic regression model was built to identify factors independently associated with the likelihood of reporting receptive syringe sharing in the past 6 months. Results A total of 1494 PWID provided data between March 2011 and May 2012. HIV prevalence differed significantly between participants in Tijuana (4.2%), CJ (7.7%), and Hermosillo (5.2%; p < 0.05). PWID from Hermosillo reported better living conditions, less frequency of drug injection, and lower prevalence of syringe sharing (p < 0.01). PWID from CJ reported a higher prevalence of syringe sharing and confiscation by police (p < 0.01). In a multivariable logistic regression model, living in Hermosillo compared to Tijuana (adjusted odds ratio [AOR] = 0.42, 95% confidence interval [CI] 0.29-0.61) and being female (AOR = 0.61, 95% CI 0.45-0.83) were protective against syringe sharing. Having used crystal meth (AOR = 1.62, 95% CI 1.24-2.13, p = 0.001), having experienced syringe confiscation by police in the last 6 months (AOR = 1.78, 95% CI 1.34-2.40), and lower perception of syringe availability (AOR = 2.15, 95% CI 1.59-2.91) were significantly associated with syringe sharing (p < 0.05). Conclusions Differences in HIV prevalence across cities reflect mainly differences in risk environments experienced by PWID, shaped by police practices, access to injection equipment, and dynamics of drug markets. Findings highlight the importance of ensuring sterile syringe availability through harm reduction services and a human rights approach to drug harms in northern Mexico and to generate better understanding of local dynamics and contexts of drug use for designing proper harm reduction programs.